Implementasi Layanan Bimbingan Kelompok dengan Teknik Mau'izhah Hasanah (Nasehat yang Baik) dalam Meningkatkan Akhlakul Karimah Pada Santri Pondok Ar Riyadh Talang Betutu Palembang : Penelitian - Ridwan Anugerah; Zhilla Jannati; Emi Puspita Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the morality of students at the Ar Riyadh Talang Betutu Islamic Boarding School in Palembang and examine the implementation of group guidance services with the mauizhah hasanah technique in improving it. The study used a qualitative approach with data collection through observation of the guidance process, interviews with ustaz and students, and document analysis. The subjects of the study were 10 students of grade VIII. Data analysis used thematic analysis which included data introduction, coding, searching and reviewing themes, defining, and compiling reports. The results showed that the morality of students was reflected in honesty, trustworthiness, patience, humility, and sincerity, with varying levels of emotional control. The implementation of group guidance with the mauizhah hasanah technique was carried out through four stages: initial planning, identification of students' needs, application of appropriate methods, and evaluation of results. The results showed that this service was effective in improving the morality of students at the Ar Riyadh Talang Betutu Islamic Boarding School in Palembang.